Exploring the Decisive Attributesof Supply Chain Planning under Uncertainty - Ming-Lang, Tseng; Ru-Jen, Lin; Huynh Le, Thuy-Vy; Anthony SF, Chiu (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
In recent years, many firms have recognized supply chain planning (SCP) as an important issue in doing business. In the electronic industry, it plays a significant role in firm’s performance. Nevertheless, a comprehensive understanding of SCP is yet to be established. Hence, the objective of this study is exploring the decisive attributes of SCP under uncertainty. By providing the aspects such as information quality, procedural quality, alignment quality and information sharing, this study contributes to determine the critical criteria which affect on SCP and thereby firm’s performance and competitive advantage. The fuzzy set theory and a decision making trial and evaluation laboratory are applied. The findings indicate that the driving aspects are information quality and procedural quality that are elements impacting on alignment quality and also contributing information sharing. This study also shows that to achieve efficiency in SCP and improve their performance, firms should focus on complete and adequate of the information exchanges as well as cooperation to plan and execute a strategy for doing business. Keywords: Supply chain planning, fuzzy set theory, decision making trial and evaluation laboratory are applied, DEMATEL